2020
DOI: 10.1186/s13018-020-02061-2
|View full text |Cite
|
Sign up to set email alerts
|

Applied anatomical study on suprascapular nerve protection in reverse total shoulder arthroplasty

Abstract: Background This study aimed to investigate the three-dimensional (3D) anatomical relationship between the suprascapular nerve and scapula, and the method of protecting the suprascapular nerve in reverse total shoulder arthroplasty (RTSA) Methods In the present study, 12 fresh adult cadaver shoulder specimens were dissected. X-ray and computed tomography (CT) were used to investigate the 3D scapular and suprascapular nerve images. Results The results revealed that the best fitting baseplate diameter was 24.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A retrospective study of patients who underwent reverse total shoulder arthroplasty was reported to have 12% risk of iatrogenic suprascapular nerve neuropathy by Jang et al [8]. The distance between the nearest point of the nerve and the osteotomy plane of 15.38 mm was found by Li et al [11]. This is important for base size selection while performing shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of patients who underwent reverse total shoulder arthroplasty was reported to have 12% risk of iatrogenic suprascapular nerve neuropathy by Jang et al [8]. The distance between the nearest point of the nerve and the osteotomy plane of 15.38 mm was found by Li et al [11]. This is important for base size selection while performing shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Also, if superior and posterior screws penetrate the scapular spine, they can act as stress risers and lead to scapular fracture. Therefore, the length and direction of superior and posterior screws should be checked carefully [21][22][23]. An oval-shaped baseplate could be better for fixation, but it can be too large for Asian patients with a relatively smaller-sized glenoid [14,20,24].…”
Section: A a B Bmentioning
confidence: 99%
“…Studies have shown that rTSA is a feasible and effective method for reconstructing bone defects after tumor resection unless the patient has axillary nerve injury and a nonfunctional deltoid muscle [ 7 9 ]. However, some problems remain with the underlying operation, such as complications, scapular notching, the repair of limb bone defects after large-scale tumor resection, and soft-tissue reconstruction after deltoid muscle resection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%